On the Effect of an Aggressive Inlet Swirl Profile on the Aero-thermal Performance of a Cooled Vane. (December 2015) - Insinna, Massimiliano; Griffini, Duccio; Salvadori, Simone; Martelli, Francesco
Abstract: A high-pressure vane equipped with a realistic film-cooling configuration has been studied. The vane is characterized by the presence of multiple rows of fan-shaped holes along pressure and suction side while the leading edge is protected by a showerhead system. Steady three-dimensional Reynolds-Averaged Navier-Stokes (RANS) simulations have been performed. A preliminary grid sensitivity analysis has been performed (with uniform inlet flow) to quantify the effect of the spatial resolution. Turbulence model has been assessed in comparison with available experiment data. The effects of a realistic inlet swirl on the aero-thermal performance of the cooling system are then investigated by means of comparison between two different kinds of simulations. The first one using a uniform inlet flow while the second one with aggressive swirl derived from the EU-funded project TATEF2. Clocking effects are also accounted for. The effect of the swirling flow in determining the coolant transport are investigated, evidencing the key role that these phenomena have in determining the effectiveness of the cooling.